2010
DOI: 10.1063/1.3511740
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer from phosphorescent blue-emitting oxidized porous silicon to rhodamine 110

Abstract: Nanocomposites consisting of oxidized porous Si (OPSi) impregnated with rhodamine 110 (Rh110) molecules are characterized in terms of luminescence properties. The photoluminescence and its polarization memory strongly indicates a trace of energy transfer from the fast blue luminescence band of OPSi to the green one of Rh110. Time-resolved experiments showed that energy transfer to Rh110 also takes place from the long-lived blue phosphorescence of OPSi. The transfer channel from nonradiative states of OPSi to R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Rhodamine 110 has a relatively narrow absorption band with a peak at about 500 nm, while unoxidized pSi emits in the red-orange region and is not expected to efficiently transfer energy to rhodamine 110, which has indeed been observed. 97 On the other hand, as noted above, OpSi luminesces in the blue-green region and, hence, can be an efficient energy donor for rhodamine 110. Analysis of PL spectra at a delay after the exciting laser pulse showed that energy transfer in the OpSi-Rh110 system occurred within a relatively long interval (B100 ms).…”
Section: Excitation and Charge Transfer In Nanocomposites Based On Psimentioning
confidence: 86%
See 3 more Smart Citations
“…Rhodamine 110 has a relatively narrow absorption band with a peak at about 500 nm, while unoxidized pSi emits in the red-orange region and is not expected to efficiently transfer energy to rhodamine 110, which has indeed been observed. 97 On the other hand, as noted above, OpSi luminesces in the blue-green region and, hence, can be an efficient energy donor for rhodamine 110. Analysis of PL spectra at a delay after the exciting laser pulse showed that energy transfer in the OpSi-Rh110 system occurred within a relatively long interval (B100 ms).…”
Section: Excitation and Charge Transfer In Nanocomposites Based On Psimentioning
confidence: 86%
“…One can select the optimal resonance conditions for a given donor and a given acceptor by varying the pore size. Many studies have dealt with pSi-based nanocomposites capable of energy transfer from pSi to the adsorbed molecules [97][98][99][100] or vice versa. [101][102][103] In terms of photonics and laser physics, of interest are studies on excitation transfer from pSi to some rhodamine dyes, 97,100,104,105 whose absorption spectra overlap with the PL spectrum of pSi.…”
Section: Excitation and Charge Transfer In Nanocomposites Based On Psimentioning
confidence: 99%
See 2 more Smart Citations
“…This blue emission includes an intrinsic phosphorescence (Ph) band which exhibits a lifetime of several seconds because of radiative transitions from triplets to ground states (10). We have also demonstrated that the energy related to the Ph emission can be efficiently transferred from OPSi to rhodamine 110 molecules (11).…”
Section: Introductionmentioning
confidence: 96%